Alternative Facts in Musicology and Vechnaya Pamyat' in Shostakovich's Symphony No. 5 - Mah, Eileen (Current Musicology, 2021)
The assertions, refutations, and counter-refutations concerning two core pieces of Richard Taruskin’s studies on Russian music—Tchaikovsky’s Symphony No. 6 and Shostakovich’s Symphony No. 5—provide a starting point for discussion about the possibilities, limits, and obligations of musicological interpretation. Moreover, an important aspect of the discussion is the phenomenon of “alternative facts,” both in publication and in pedagogy, and possibly in music itself. Taruskin argues against the logical fallacies of overly specific or overly simplistic interpretations, but hesitates to fully interpret certain music himself, thereby participating in the web of alternative facts. Taruskin refutes popular myths about biographical meanings in Tchaikovsky’s symphony, but in so doing, also seems to reject a tragic reading of any kind. He explains away various musical structures and extroversive references, but fails to explore why those elements are in fact present. As for Shostakovich’s symphony, Taruskin notes its saturation with musical topics, but ignores their allusive specificity, downplaying their significance altogether for what he calls their transferability. Yet Taruskin himself identifies an allusion to a specific Orthodox hymn, and therefrom draws specific conclusions. His evidence for calling the passage a “literal imitation” is actually flawed, but a truly literal quotation of this very hymn may be present throughout the entire symphony, and may act as a sort of species of alternative fact itself. In any case, something that specific, and its placement in the symphonic structure, deserve notice and demand specificity of interpretation.